Baricitinib plus dexamethasone compared to dexamethasone for the treatment of severe COVID-19 pneumonia: A retrospective analysis - Pérez Alba, Eduardo; Nuzzolo Shihadeh, Laura Marina; Aguirre García, Gloria Mayela; Espinosa Mora, Jaime Eugenio; Lecona García, Juan Diego; Flores Pérez, Rómulo Omar; Mendoza Garza, Marisela; Camacho Ortiz, Adrián (Scientific Communications International, 2021)
Objective: We aimed to analyze clinical outcomes from patients with severe COVID-19 pneumonia that received either baricitinib plus dexamethasone or dexamethasone monotherapy.